Cement-improved lake bed sedimentary soil for road construction. Issue 3 (28th June 2019) - Chompoorat, Thanakorn; Maikhun, Thacchai; Likitlersuang, Suched
Abstract : Phayao Lake, the largest lake in the north of Thailand, supplies water for consumption and irrigation in the region. Currently, the lake is faced with serious problems as it is becoming shallow with a consequent decrease in the volume of water. Every year the local government invests a lot of resources to dredge and pump the lake bed of sediments. However, it is difficult to find suitable landfill areas to dump such large quantities of sedimentary soil. The purpose of this study was to improve the engineering properties of sedimentary soil using Portland cement for possible use in road construction. The sedimentary soils were mixed with cement in a 3–10% proportion by weight. The strength and durability of the improved soil were examined using unconfined compression and durability tests, respectively. A long-term strength improvement was observed and well-fitted to a power function. Soil−cement losses due to multiple wet−dry cycles were examined by means of durability tests. Finally, suitable cement percentages for sediment improvement are suggested to achieve the requirements for road base and subbase materials.